Dexamethasone prevents granulocyte-macrophage colony-stimulating factor-induced nuclear factor-κB activation, inducible nitric oxide synthase expression and nitric oxide production in a skin dendritic cell line - Ana Luísa Vital; Margarida Gonçalo; M. Teresa Cruz; Américo Figueiredo; Carlos B. Duarte; M. Celeste Lopes (Mediators of Inflammation, 2003)
Aims: Nitric oxide (NO) has been increasingly implicated in inflammatory skin diseases, namely in allergic contact dermatitis. In this work, we investigated the effect of dexamethasone on NO production induced by the epidermal cytokine granulocyte-macrophage colony-stimulating factor (GM-CSF) in a mouse fetal skin dendritic cell line.